ACTIVITIES ASSESSMENT AS A TOOL TO MEASURE STUDENTS’ OBSERVATION SKILLS IN SCIENCE LEARNING - Dewanti, Binar Ayu (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2019)
Observation skills are one of the basic skills students must possess in science learning. Through observation skills, students are able to identify facts or initial knowledge before going on to the next stage of the science process skills. In science learning, student observation skills can be observed and measured through all learning activities both in the classroom and in the laboratory (practicum) by using the activity assessment sheet. Activity assessment sheet is a derivative form of performance assessment consisting of 1) student identity, 2) assessment instructions, 3) basic competencies, 4) assessment table (sub-material, observed observation skills, scores, and information), 5) formulation acquisition of final score, and 6) assessment rubric. The assessment sheet for this activity has been tested on 44 junior high school students and the average results reached more than 50% of students showing the highest score of observation skills. Thus, the activity assessment sheet can be said to be used to measure student observation skills.